Scalp microbiome as a key factor in hair growth: innovative therapeutic strategies - Malaniuk, Khrystyna (Annals of Mechnikov's Institute, 2025)
Introduction. Disruption of the scalp microbiome is one of the key factors in the development of seborrheic dermatitis, itching, scaling, increased oiliness and diffuse hair loss. Traditional aggressive treatment approaches using antifungal, antibacterial or corticosteroid agents are often accompanied by side effects, disruption of the skin microflora and relapses. In this context, there is a need for alternative, microbiome-friendly innovative therapeutic strategies. The purpose of the study was to evaluate the effectiveness of probiotics, prebiotics, postbiotics and recombinant peptides in the care of scalps with a disturbed microbiome, as well as to determine their effect on symptoms, microbiota structure and hair growth. Materials and methods of the study included a systematic review of the literature on the assessment of dynamics in individuals with scalp microbiome disorders, the use of molecular diagnostic methods, trichoscopy, questionnaires and dermatological indices. analysis of the composition of cosmetic products, the results obtained were analyzed using descriptive statistics. As a result, it was found that microbiome-friendly products help reduce itching, redness, peeling, normalize sebum secretion and improve subjective comfort. Also recorded was an increase in microbiome diversity, a decrease in the concentration of Cutibacterium acnes and Malassezia spp., activation of the anagen phase of hair growth, a decrease in telogen effluvium and positive changes in diffuse alopecia. Conclusions. The comparative analysis confirmed the advantages of innovative microbiome-friendly therapy over traditional aggressive therapy: higher safety, better tolerability, a lasting effect and the possibility of personalizing treatment. The data obtained indicate the feasibility of introducing such products into clinical practice for the treatment of dysbiotic scalp conditions.